Multilayer structure having enhanced adhesive bond strength and articles including same
A multilayer structure with a matte-surfaced biaxially oriented polyethylene film and adhesive bonding to a sealant film addresses the adhesion issues in BOPE films, enhancing adhesive bond strength and packaging integrity.
Patent Information
- Application Number
- JP2023513188
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-08-27
- Publication Date
- 2024-12-16
- Estimated Expiration
- 2040-08-27
AI Technical Summary
Multilayer structures incorporating biaxially-oriented polyethylene (BOPE) films face challenges due to poor adhesion between non-polar polyethylene and polar adhesives, leading to low adhesive bond strength and film delamination, which compromises packaging integrity.
A multilayer structure comprising a biaxially oriented polyethylene film with a matte skin layer, a sealant film, and an adhesive that adheres the sealant film to the matte surface, enhancing adhesive bond strength.
The solution results in significantly higher adhesive bond strength, improving packaging integrity by ensuring strong adhesion between layers.
Smart Images

Figure 0007600376000001 
Figure 0007600376000002 
Figure 0007600376000003
Abstract
Description
[Technical field]
[0001] FIELD OF THE DISCLOSURE Embodiments of the present disclosure relate generally to multilayer structures, and more specifically to multilayer structures comprising biaxially oriented polyethylene films.
[0002] Introduction Multilayer structures incorporating biaxially-oriented polyethylene (BOPE) films are becoming more common in the packaging industry. BOPE films have excellent mechanical and optical properties, which are in part the result of the high orientation of the film in both the machine and cross directions. However, problems exist when forming multilayer structures containing BOPE films. In particular, BOPE films contain polyethylene, a non-polar polymer that exhibits poor adhesion to polar adhesives. This incompatibility makes it difficult for BOPE films to adhere to other films during lamination, and low adhesive bonds between the films can cause poor package integrity due to film delamination. Thus, there remains a need for multilayer structures containing BOPE films that exhibit improved adhesive bonds. Summary of the Invention
[0003] The present invention provides a multi-layer structure comprising a biaxially oriented polyethylene film, a seleant film, and an adhesive. In an embodiment, the biaxially oriented polyethylene film has a skin layer with a matte surface, and the matte surface of the skin layer is adhered to a sealant film via an adhesive to provide a multi-layer structure exhibiting desirable properties such as high adhesive bond strength.
[0004] In one aspect, the invention provides a multilayer structure comprising: (a) a biaxially oriented polyethylene film comprising a skin layer having a matte surface and a core, the core comprising one or more core layers; (b) a sealant film; and (c) an adhesive that adheres the sealant film to the matte surface of the skin layer of the biaxially oriented polyethylene film.
[0005] Also disclosed herein is an article comprising a multi-layer structure according to an embodiment disclosed herein.
[0006] These and other embodiments are described in greater detail in the Detailed Description. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0007] Aspects of the disclosed multi-layer structures are described in more detail below. The multi-layer structures of the present disclosure may have a wide variety of applications, including, for example, pouches, stand-up pouches, pillow pouches, bulk bags, prefabricated packaging, sachets, etc. However, the present disclosure should not be construed as being limited to the embodiments described below.
[0008] As used herein, the term "polymer" refers to a polymeric compound prepared by polymerizing monomers, whether of the same or different types. Thus, the generic term "polymer" encompasses the term homopolymer (used to refer to a polymer prepared from only one type of monomer), and the terms copolymer or interpolymer. Trace amounts of impurities (e.g., catalyst residues) may be introduced into and / or within the polymer. The polymer may be a single polymer, a polymer blend, or a polymer mixture, including a mixture of polymers formed in situ during polymerization.
[0009] As used herein, the term "polypropylene" or "propylene-based polymer" refers to a polymer that contains more than 50 weight percent polymerized propylene monomer (based on the total amount of polymerizable monomers) and may optionally contain at least one comonomer.
[0010] As used herein, the term "polyethylene" or "ethylene-based polymer" shall mean a polymer containing a majority (>50 mol%) of units derived from ethylene monomer. This includes polyethylene homopolymers or copolymers (meaning units derived from two or more comonomers). Common forms of polyethylene known in the art include low density polyethylene (LDPE), linear low density polyethylene (LLDPE), ultra low density polyethylene (ULDPE), very low density polyethylene (VLDPE), single-site catalyzed linear low density polyethylene (m-LLDPE), including both linear and substantially linear low density resins, ethylene-based plastomers (POP) and ethylene-based elastomers (POE), medium density polyethylene (MDPE), and high density polyethylene (HDPE). These polyethylene materials are generally known in the art. However, the following description may be helpful in understanding the differences between some of these different polyethylene resins.
[0011] The term "LDPE", which may also be referred to as "high pressure ethylene polymer", or "highly branched polyethylene", is defined to mean that the polymer is partially or fully homopolymerized or copolymerized in an autoclave or tubular reactor at pressures in excess of 14,500 psi (100 MPa) using a free radical initiator, such as peroxide (see, for example, U.S. Pat. No. 4,599,392, incorporated by reference). LDPE resins typically have densities in the range of 0.916 to 0.935 g / cc.
[0012] The term "LLDPE" includes both resins made using single-site catalysts, including, but not limited to, traditional Ziegler-Natta catalyst systems and chromium-based catalysts, as well as mono- or bis-cyclopentadienyl catalysts (typically referred to as metallocenes) and constrained geometry catalysts, phosphinimine catalysts and polyaryloxy ether catalysts (typically referred to as bisphenylphenoxy), and includes linear, substantially linear, or heterogeneous polyethylene copolymers or homopolymers. LLDPE contains less long chain branching than LDPE and includes substantially linear ethylene polymers as further defined in U.S. Patent Nos. 5,272,236, 5,278,272, 5,582,923, and 5,733,155, homogeneously branched linear ethylene polymer compositions such as those in U.S. Patent No. 3,645,992, heterogeneously branched ethylene polymers such as those prepared according to the process disclosed in U.S. Patent No. 4,076,698, and / or blends thereof (such as those disclosed in U.S. Patent No. 3,914,342 or U.S. Patent No. 5,854,045). LLDPE may be made via gas phase, solution phase, or slurry polymerization, or any combination thereof, using any type of reactor or reactor configuration known in the art.
[0013] The term "MDPE" refers to polyethylene having a density of 0.926 to 0.935 g / cc. "MDPE" is typically produced using chromium or Ziegler-Natta catalysts, or using single-site catalysts, including but not limited to substituted mono- or bis-cyclopentadienyl catalysts (typically referred to as metallocenes), constrained geometry catalysts, phosphinimine catalysts, and polyaryloxy ether catalysts (typically referred to as bisphenylphenoxy), and typically has a molecular weight distribution ("MWD") greater than 2.5.
[0014] The term "HDPE" refers to polyethylene having a density greater than about 0.935 g / cc up to about 0.980 g / cc that is generally prepared using single-site catalysts including, but not limited to, Ziegler-Natta catalysts, chromium catalysts, or substituted mono- or bis-cyclopentadienyl catalysts (typically referred to as metallocenes), constrained geometry catalysts, phosphinimine catalysts, and polyaryloxy ether catalysts (typically referred to as bisphenylphenoxy).
[0015] The term "ULDPE" refers to polyethylene having a density between 0.855 and 0.915 g / cc, generally prepared using single-site catalysts including, but not limited to, Ziegler-Natta, chromium, or substituted mono- or bis-cyclopentadienyl catalysts (typically referred to as metallocenes), constrained geometry catalysts, phosphinimine catalysts, and polyaryloxy ether catalysts (typically referred to as bisphenylphenoxy). ULDPE includes, but is not limited to, polyethylene (ethylene-based) plastomers and polyethylene (ethylene-based) elastomers.
[0016] As used herein, the term "multilayer structure" refers to any structure having two or more layers. For example, a multilayer structure may have 2, 3, 4, 5, or more layers. A multilayer structure may be described as having layers designated by letters. For example, a three-layer structure having a core layer B and two outer layers A and C may be designated as A / B / C. Similarly, a structure having two core layers B and C and two outer layers A and D may be designated as A / B / C / D.
[0017] As used herein, the term "matte surface" refers to a surface that has a matte appearance rather than a glossy appearance. A matte surface has one or both of the following: (1) a gloss of less than 50% and (2) a haze of greater than 45%.
[0018] The terms "comprising," "including," "having," and their derivatives are not intended to exclude the presence of any additional components, steps, or procedures, whether or not they are specifically disclosed. For the avoidance of any doubt, all compositions claimed through the use of the term "comprising" may include any additional additives, adjuvants, or compounds, whether polymeric or otherwise, unless otherwise stated to the contrary. In contrast, the term "consisting essentially of" excludes from the scope of any succeeding description any other component, step, or procedure, except those that are not essential to operability. The term "consisting of" excludes any component, step, or procedure not specifically delineated or listed.
[0019] BOPE Film In an embodiment, the multilayer structure of the present invention comprises (a) a biaxially oriented polyethylene film, (b) a sealant film, and (c) an adhesive. The biaxially oriented polyethylene film comprises a skin layer having a matte surface and a core, the core comprising one or more layers. In one embodiment, the biaxially oriented polyethylene film comprises two skin layers, including a skin layer having a matte surface, and at least one core layer. In an embodiment where there are two skin layers, the skin layers can have the same or different compositions, so long as at least one skin layer has a matte surface. The biaxially oriented polyethylene film can comprise 3, or 4, or 5, or 6, or 7, or 8, or 9, or 10, or more layers.
[0020] In an embodiment, the biaxially oriented polyethylene film is stretched in the machine direction with a stretch ratio of 2:1 to 6:1 and in the transverse direction with a stretch ratio of 2:1 to 9:1. In one embodiment, the biaxially oriented polyethylene film is stretched in the machine direction with a stretch ratio of 3:1 to 5:1 and in the transverse direction with a stretch ratio of 3:1 to 8:1.
[0021] The biaxially oriented polyethylene film according to the embodiments disclosed herein can be formed using a tenter frame sequential stretching process. Such processes for forming biaxially oriented polyethylene films are generally known to those skilled in the art. In other embodiments, the biaxially oriented polyethylene film can also be biaxially oriented using other techniques known to those skilled in the art, such as a double bubble stretching process, based on the teachings herein.
[0022] Generally, in the tenter frame sequential biaxial stretching process, the tenter frame is incorporated as part of a multi-layer coextrusion line. After extrusion from a flat die, the film is cooled on a chill roll and immersed in a water bath filled with room temperature water. The cast film is then passed over a series of rollers with different rotation speeds to achieve stretching in the machine direction. There are several pairs of rollers in the MD stretching segment of the production line, all of which are oil heated. The pairs of rollers operate sequentially as preheating rollers, stretching rollers, and relaxation and annealing rollers. The temperature of each pair of rollers is controlled separately. After stretching in the machine direction, the film web is passed through a tenter frame hot air oven with heating zones to perform stretching in the transverse direction. The first few zones are for preheating, followed by a zone for stretching, and then a final zone for annealing.
[0023] The biaxially oriented polyethylene film according to the embodiments disclosed herein includes a skin layer having a matte surface. In an embodiment, the skin layer having a matte surface includes 20-80 wt% of an ethylene-based polymer and 80-20 wt% of a propylene-based polymer, based on the total weight of the skin layer, and each of the ethylene-based polymer and the propylene-based polymer has a storage modulus, and the difference between the storage modulus of the ethylene-based polymer and the propylene-based polymer is greater than 40 megapascals (MPa) at 110° C. and greater than 18 MPa at 120° C. The skin layer having a matte surface can include 20-80 wt%, 30-70 wt%, 40-60 wt%, or 45-55 wt% of the ethylene-based polymer, and can include 80-20 wt%, 70-30 wt%, 60-40 wt%, or 55-45 wt% of the propylene-based polymer, the weight percentages being based on the total weight of the skin layer. In embodiments, the difference in storage modulus between the ethylene-based polymer and the propylene-based polymer may be greater than 40 MPa at 110° C., greater than 50 MPa at 110° C., greater than 60 MPa at 110° C., greater than 70 MPa at 110° C., greater than 80 MPa at 110° C., greater than 90 MPa at 110° C., greater than 100 MPa at 110° C., greater than 110 MPa at 110° C., or greater than 120 MPa at 110° C. In embodiments, the difference in storage modulus between the ethylene-based polymer and the propylene-based polymer may be greater than 18 MPa at 120° C., greater than 30 MPa at 120° C., greater than 40 MPa at 120° C., greater than 50 MPa at 120° C., greater than 60 MPa at 120° C., or greater than 70 MPa at 120° C. Storage moduli at 110° C. and 120° C. can be measured according to the test methods described below.
[0024] In an embodiment, the matte surface of the skin layer has a gloss of less than 50% when measured by ASTM D2457 at an angle of 45°. All individual values and subranges less than 50% are disclosed and included herein. For example, the matte surface of the skin layer can have a gloss of less than 50%, less than 40%, less than 30%, less than 20%, or less than 15%, where the gloss can be measured by ASTM D2457 at an angle of 45°.
[0025] In an embodiment, the matte surface of the skin layer has a haze of greater than 45% as measured by ASTM D1003. All individual values and subranges greater than 45% are disclosed and included herein. For example, the matte surface of the skin layer can have a haze of greater than 45%, greater than 46%, greater than 47%, greater than 48%, greater than 49%, or greater than 50%, as measured by ASTM D1003.
[0026] In an embodiment, the skin layer having a matte surface comprises an ethylene-based polymer having a density of 0.900 to 0.960 g / cc. All individual values and ranges of density from 0.900 to 0.960 g / cc are disclosed and included herein. For example, in an embodiment, the ethylene-based polymer of the skin layer has a density of 0.900 to 0.960 g / cc, 0.900 to 0.950 g / cc, 0.900 to 0.940 g / cc, 0.900 to 0.930 g / cc, or 0.900 to 0.920 g / cc. In an embodiment, the ethylene-based polymer of the skin layer is a linear low density polyethylene having a density of 0.910 to 0.940 g / cc.
[0027] In one embodiment, the skin layer comprises an ethylene / α-olefin copolymer and a propylene / ethylene copolymer, each of the ethylene / α-olefin copolymer and the propylene / ethylene copolymer having a storage modulus, the difference between the storage modulus of the ethylene / α-olefin copolymer and the propylene / ethylene copolymer being 110 to 130 megapascals (MPa) at 110° and 70 to 80 MPa at 120° C., and the matte surface of the skin layer has (i) a gloss of 3% to 15% as measured by ASTM D2457 at a 45° angle, or (ii) a haze of greater than 45% as measured by ASTM D1003.
[0028] Examples of ethylene-based polymers or ethylene / α-olefin copolymers that can be used in the skin layers include those commercially available from The Dow Chemical Company under the name ELITE™, including, for example, ELITE™ 5815.
[0029] Examples of propylene-based polymers or propylene / ethylene copolymers that can be used for the skin layers include those commercially available from Hyosung Corporation under the name TOPILENE™ PPR R200P.
[0030] The biaxially oriented polyethylene film comprises a core comprising one or more core layers. In an embodiment, the core of the biaxially oriented polyethylene film comprises one, or two, or three, or more core layers. In an embodiment, the core of the biaxially oriented polyethylene film comprises at least 50% by weight of an ethylene-based polymer, based on the total weight of all core layers. All individual values and subranges of at least 50% by weight are disclosed and included herein. For example, the core of the biaxially oriented polyethylene film can comprise at least 50% by weight, at least 60% by weight, at least 70% by weight, at least 80% by weight, at least 90% by weight, at least 95% by weight, at least 99% by weight, or at least 99.9% by weight of an ethylene-based polymer, the weight percentages being based on the total weight of all core layers.
[0031] Biaxially oriented polyethylene films according to embodiments disclosed herein can have a variety of thicknesses, depending, for example, on the number of layers. For example, in embodiments, the biaxially oriented polyethylene film can have a thickness of 5 to 200 microns, or alternatively, 15 to 100 microns. In embodiments, the core of the biaxially oriented polyethylene film comprises at least 50%, at least 60%, at least 70%, at least 80%, or at least 90% of the total thickness of the biaxially oriented polyethylene film.
[0032] Sealant Film The multilayer structure of the present invention includes a sealant film. The sealant film is formed separately from the biaxially oriented polyethylene film. Therefore, the sealant film is not biaxially oriented and is adhered to the matte surface of the skin layer of the biaxially oriented polyethylene film via an adhesive.
[0033] The composition and configuration of the sealant film disclosed herein is not particularly limited. In an embodiment, the sealant film can include one, or two, or three, or four, or five, or six, or more layers. The sealant film can be a blown film or a cast film. The sealant film can have a variety of thicknesses, for example, depending on the number of layers of the sealant film. For example, in an embodiment, the sealant film can have a thickness of 5 to 200 microns, or alternatively, 15 to 100 microns.
[0034] In an embodiment, the sealant film is a monolayer film.In another embodiment, the sealant film is a multilayer film.In an embodiment, one or more layers of the sealant film can include any number of polymers, for example, polyethylene, polypropylene, polyester, polyamide, or ethylene vinyl alcohol copolymer, depending on, for example, the intended use or desired properties of the film.
[0035] In embodiments, the sealant film comprises at least 50% by weight polyethylene, or at least 60% by weight polyethylene, or at least 70% by weight polyethylene, or at least 80% by weight polyethylene, or at least 90% by weight polyethylene, or at least 95% by weight polyethylene, based on the total weight of the sealant film.
[0036] In an embodiment, the sealant film may include a layer that includes at least 20% by weight of polyolefin plastomer, polyolefin elastomer, very low density polyethylene, ethylene acetate copolymer, ethylene acrylic acid copolymer, or ethylene acrylate copolymer, based on the total weight of the layer. All individual values and subranges of at least 20% by weight are disclosed and included herein. For example, the sealant film may include a layer that includes at least 20% by weight, at least 30% by weight, at least 40% by weight, at least 50% by weight, at least 60% by weight, at least 70% by weight, at least 80% by weight, at least 90% by weight, at least 95% by weight, or at least 99% by weight of polyolefin plastomer, polyolefin elastomer, very low density polyethylene, ethylene acetate copolymer, ethylene acrylic acid copolymer, or ethylene acrylate copolymer, the weight percentage being based on the total weight of the layer of the sealant film.
[0037] In such embodiments where the layer of the sealant film has at least 20% by weight of polyolefin plastomer, polyolefin elastomer, very low density polyethylene, ethylene acetate copolymer, ethylene acrylic acid copolymer, or ethylene acrylate copolymer, the layer of the sealant film can further comprise low density polyethylene and / or linear low density polyethylene. For example, in one embodiment, the sealant layer comprises a layer comprising: (a) 20-100% by weight of polyolefin plastomer, polyolefin elastomer, very low density polyethylene, ethylene acetate copolymer, ethylene acrylic acid copolymer, or ethylene acrylate copolymer; (b) 0-30% by weight of low density polyethylene; and (c) 0-80% by weight of linear low density polyethylene, the weight percentages being based on the total weight of the layer of the sealant film. All individual values and subranges of 0-30% by weight of low density polyethylene are disclosed and included herein. For example, the sealant layer can include a layer containing 0-30 wt%, 5-25 wt%, or 10-20 wt% low density polyethylene, where the weight percentages are based on the total weight of the layer of the sealant film. All individual values and subranges of 0-80 wt% linear low density polyethylene are disclosed and included herein. For example, the sealant layer can include a layer containing 0-80 wt%, 10-70 wt%, 20-60 wt%, or 30-50 wt% linear low density polyethylene, where the weight percentages are based on the total weight of the layer of the sealant film.
[0038] When the sealant film includes a polyolefin plastomer, the polyolefin plastomer can be a polyethylene plastomer or a polypropylene plastomer. Polyolefin plastomers include resins made using single-site catalysts, such as metallocene and constrained geometry catalysts. The polyolefin plastomer has a density of 0.885 to 0.915 g / cc. All individual values and subranges between 0.885 g / cc and 0.915 g / cc are included herein and disclosed herein, for example, the density of the polyolefin plastomer can have a lower limit of 0.895, 0.900, or 0.905 g / cc and an upper limit of 0.905, 0.910, or 0.915 g / cc. In some embodiments, the polyolefin plastomer has a density of 0.890 to 0.910 g / cc.
[0039] In some embodiments, the polyolefin plastomer has a melt index (I2) of up to 20 g / 10 min. All individual values and subranges of up to 20 g / 10 min are included and disclosed herein. For example, the polyolefin plastomer can have a melt index (I2) of 1.0, 2.0, 3.0, 4.0, 5.0, 6.0, 7.0, 8.0, 9.0, 10.0, 11, 12, 13, 14, 15, 16, 17, 18, 19, or up to an upper limit of 20 g / 10 min. In certain aspects of the present invention, the polyolefin plastomer has a melt index, I2, with a lower limit of 0.5 g / 10 min.
[0040] Examples of polyolefin plastomers that can be used in the sealant film include those commercially available from The Dow Chemical Company under the AFFINITY™ name, including, for example, AFFINITY™ PL 1881G and AFFINITY™ PF1140G.
[0041] When the sealant film includes a polyolefin elastomer, the polyolefin elastomer can be a polyethylene elastomer or a polypropylene elastomer. The polyolefin elastomer has a density of 0.857 to 0.885 g / cc. All individual values and subranges between 0.857 and 0.885 g / cc are included and disclosed herein, for example, the density of the polyolefin elastomer can have a lower limit of 0.857, 0.860, 0.865, 0.870, or 0.875 g / cc and an upper limit of 0.870, 0.875, 0.880, or 0.885 g / cc. In some embodiments, the polyolefin elastomer has a density of 0.860 to 0.880 g / cc.
[0042] In some embodiments, the polyolefin elastomer has a melt index (I2) of up to 20 g / 10 min. All individual values and subranges up to 20 g / 10 min are included and disclosed herein. For example, the polyolefin elastomer can have an upper melt index (I2) of 1.0, 2.0, 3.0, 4.0, 5.0, 6.0, 7.0, 8.0, 9.0, 10.0, 11, 12, 13, 14, 15, 16, 17, 18, 19, or 20 g / 10 min. In certain aspects of the present invention, the polyolefin elastomer has a lower melt index, I2, of 0.5 g / 10 min.
[0043] Examples of polyolefin elastomers that can be used in the sealant film include those commercially available from The Dow Chemical Company under the AFFINITY™ name, including, for example, AFFINITY™ EG8100G and AFFINITY™ EG8200G.
[0044] When the sealant film comprises ultra low density polyethylene (ULDPE), the ULDPE has a density of 0.880 to 0.915 g / cc. All individual values and subranges between 0.880 g / cc and 0.915 g / cc are included herein and disclosed herein, for example, the density of the ULDPE can have a lower limit of 0.880, 0.885, 0.890, 0.895, 0.900, or 0.905 g / cc and an upper limit of 0.895, 0.900, 0.905, 0.910, 0.912, or 0.915 g / cc. In some embodiments, the ULDPE has a density of 0.885 to 0.910 g / cc.
[0045] In some embodiments, the ULDPE has a melt index (I2) of up to 20 g / 10 min. All individual values and subranges of up to 20 g / 10 min are included and disclosed herein. For example, the ULDPE can have a melt index of 1.0, 2.0, 3.0, 4.0, 5.0, 6.0, 7.0, 8.0, 9.0, 10.0, 11, 12, 13, 14, 15, 16, 17, 18, 19, or up to an upper limit of 20 g / 10 min. In certain aspects of the invention, the ULDPE has a melt index, I2, with a lower limit of 0.5 g / 10 min.
[0046] Examples of ULDPE that may be used in the sealant film include those commercially available from The Dow Chemical Company under the ATTANE™ name, including, for example, ATTANE™ 4201G and ATTANE™ 4203.
[0047] When the sealant film includes an ethylene acetate copolymer, the ethylene acetate copolymer can be, for example, ethylene vinyl acetate. In some embodiments, the ethylene acetate copolymer can have an acetate content of 5% to 40%. The ethylene acetate copolymer has a density of 0.920 to 0.970 g / cc. All individual values and subranges between 0.920 g / cc and 0.970 g / cc are included and disclosed herein, for example, the density of the ethylene acetate copolymer can have a lower limit of 0.920, 0.925, 0.930, 0.935, 0.940 g / cc and an upper limit of 0.945, 0.950, 0.955, 0.960, 0.965, or 0.970 g / cc. In some embodiments, the ethylene acetate copolymer has a density of 0.930 to 0.950 g / cc.
[0048] In some embodiments, the ethylene acetate copolymer has a melt index (I2) of up to 20 g / 10 min. All individual values and subranges up to 20 g / 10 min are included and disclosed herein. For example, the ethylene acetate copolymer can have a melt index of 1.0, 2.0, 3.0, 4.0, 5.0, 6.0, 7.0, 8.0, 9.0, 10.0, 11, 12, 13, 14, 15, 16, 17, 18, 19, or up to an upper limit of 20 g / 10 min. In certain aspects of the present invention, the ethylene acetate copolymer has a melt index, I2, with a lower limit of 0.25 g / 10 min.
[0049] Examples of ethylene acetate copolymers that can be used in the sealant film include those commercially available from Dupont-Mitsui Polychemical Co., Ltd. under the name Evaflex, including, for example, Evaflex 410 and Evaflex 460.
[0050] When the sealant film comprises an ethylene acrylic acid copolymer, the ethylene acrylic acid copolymer has a density of 0.920 to 0.960 g / cc. All individual values and subranges between 0.920 g / cc and 0.960 g / cc are included and disclosed herein, for example, the density of the ethylene acrylic acid copolymer can have a lower limit of 0.920, 0.925, or 0.930 g / cc and an upper limit of 0.935, 0.940, 0.945, 0.950, 0.955, or 0.960 g / cc. In some embodiments, the ethylene acrylic acid copolymer has a density of 0.930 to 0.938 g / cc.
[0051] In some embodiments, the ethylene acrylic acid copolymer has a melt index (I2) of up to 20 g / 10 min. All individual values and subranges of up to 20 g / 10 min are included and disclosed herein. For example, the ethylene acrylic acid copolymer can have a melt index (I2) of 1.0, 2.0, 3.0, 4.0, 5.0, 6.0, 7.0, 8.0, 9.0, 10.0, 11, 12, 13, 14, 15, 16, 17, 18, 19, or up to an upper limit of 20 g / 10 min. In certain aspects of the invention, the ethylene acrylic acid copolymer has a melt index, I2, with a lower limit of 0.25 g / 10 min. In some embodiments including ethylene acrylic acid copolymer, the ethylene acrylic acid copolymer can have an acrylic acid content of 3% to 20%.
[0052] Examples of ethylene acrylic acid copolymers that may be used in the sealant films include those commercially available from The Dow Chemical Company under the PRIMACOR™ name, including, for example, PRIMACOR™ 3003 and PRIMACOR™ 3004.
[0053] When the sealant film includes an ethylene acrylate copolymer, the ethylene acrylate copolymer can be, for example, ethylene ethyl acrylate. The ethylene acrylate copolymer has a density of 0.920 to 0.955 g / cc. All individual values and subranges between 0.920 g / cc and 0.955 g / cc are included and disclosed herein, for example, the density of the ethylene acrylate copolymer can have a lower limit of 0.920, 0.925, 0.930, 0.935, or 0.940 g / cc and an upper limit of 0.930, 0.935, 0.940, 0.945, 0.950, or 0.955 g / cc. In some embodiments, the ethylene acrylate copolymer has a density of 0.930 to 0.940 g / cc. In some embodiments including ethylene acrylate copolymers, the ethylene acrylate copolymers may have an acrylate content of 10% to 25%.
[0054] In some embodiments, the ethylene acrylate copolymer has a melt index (I2) of up to 20 g / 10 min. All individual values and subranges up to 20 g / 10 min are included and disclosed herein. For example, the ethylene acrylate copolymer can have a melt index (I2) of 1.0, 2.0, 3.0, 4.0, 5.0, 6.0, 7.0, 8.0, 9.0, 10.0, 11, 12, 13, 14, 15, 16, 17, 18, 19, or up to an upper limit of 20 g / 10 min. In certain aspects of the present invention, the ethylene acrylate copolymer has a melt index, I2, with a lower limit of 0.25 g / 10 min.
[0055] Examples of ethylene acrylate copolymers that may be used in the sealant film include those commercially available from The Dow Chemical Company under the name AMPLIFY™ EA, including, for example, AMPLIFY™ EA 101 and AMPLIFY™ EA 100.
[0056] When the sealant film comprises low density polyethylene (LDPE), the LDPE can have a density of 0.916 to 0.940 g / cc. All individual values and subranges between 0.916 g / cc and 0.940 g / cc are included and disclosed herein, for example, the density of the LDPE can have a lower limit of 0.916, 0.920, 0.924, 0.928, or 0.930 g / cc and an upper limit of 0.925, 0.930, 0.935, or 0.940 g / cc. In some embodiments, the LDPE has a density of 0.916 to 0.930 g / cc. In some embodiments, the LDPE has a melt index (I2) of up to 20 g / 10 min. All individual values and subranges between 0.916 g / cc and 0.940 g / cc are included and disclosed herein. For example, the LDPE can have a melt index of 1.0, 2.0, 3.0, 4.0, 5.0, 6.0, 7.0, 8.0, 9.0, 10.0, 11, 12, 13, 14, 15, 16, 17, 18, 19, or up to an upper limit of 20 g / 10 min. In certain aspects of the invention, the LDPE has a melt index, I2, with a lower limit of 0.25 g / 10 min.
[0057] In an embodiment where the sealant film is a multilayer film, the sealant film can include a second layer comprising an ethylene-based polymer having a density of 0.900 to 0.960 g / cc. In such an embodiment, the second layer can include up to 100% by weight of an ethylene-based polymer. In such an embodiment, the ethylene-based polymer of the second layer can have a melt index, I2, of up to 20 g / 10 min. All individual values and subranges up to 20 g / 10 min are included and disclosed herein. For example, the ethylene-based polymer can have a melt index, I2, of 1.0, 2.0, 3.0, 4.0, 5.0, 6.0, 7.0, 8.0, 9.0, 10.0, 11, 12, 13, 14, 15, 16, 17, 18, 19, or up to an upper limit of 20 g / 10 min. In a particular aspect of the invention, the ethylene-based polymer has a melt index, I2, with a lower limit of 0.25 g / 10 min.
[0058] In embodiments, for example, depending on the end use application, the sealant film may be corona treated or printed using techniques known to those skilled in the art, either before or after lamination to the matte surface of the skin layer of biaxially oriented polyethylene film.
[0059] The sealant film may have various properties. In an embodiment, the sealant film has a heat seal initiation temperature of less than 120°C, which can be measured according to the test method described below. In an embodiment, the sealant film may have a heat seal initiation temperature of less than 115°C, or alternatively less than 110°C, or alternatively less than 105°C, or alternatively less than 100°C, which can be measured according to the test method described below.
[0060] glue The multi-layer structure includes an adhesive. The adhesive adheres the sealant film to the matte surface of the skin layer of the biaxially oriented polyethylene film. The adhesive is not a tie layer that can be co-extruded between the biaxially oriented polyethylene film and the sealant film. Rather, the biaxially oriented polyethylene film and the sealant film are formed separately and then the adhesive is used to adhere the sealant film to the matte surface of the skin layer of the biaxially oriented polyethylene film.
[0061] The adhesive may be any adhesive suitable for adhering the sealant film to the matte surface of the skin layer of the biaxially oriented polyethylene film. In embodiments, the adhesive comprises a solventless adhesive, a water-based adhesive, or a solvent-based adhesive. The matte surface of the skin layer of the biaxially oriented polyethylene film may be adhered to the Celent film using any process known to one of skill in the art based on the teachings herein, including, for example, using a dry or wet or solventless lamination process, or using a manual or mechanical lamination process.
[0062] The adhesive coat weight can depend on several factors including, for example, the thickness of the biaxially oriented polyethylene film, the thickness of the sealant film, the desired thickness of the multi-layer structure, and the type of adhesive used. In embodiments, the adhesive is applied at an adhesive coat weight of 1 to 5 gsm, 1 to 4 gsm, or 1 to 3 gsm.
[0063] Examples of adhesives that can be used in accordance with embodiments of the present invention include MOR-FREE™, ADCOTE™, including, for example, MOR-FREE™ 709A / B, ROBOND™ L168 / CR3A, ROBOND™ L188 / CR3A, ADCOTE™ D516A / F, and ADCOTE™ 545S / F. (trademark), and ROBOND (trademark) available from The Dow Chemical Company.
[0064] In embodiments, the multilayer structure of the present invention can include other layers. For example, the multilayer structure of the present invention can include, in some embodiments, one or more additional biaxially oriented polyethylene films, one or more additional Celent films, and / or one or more additional adhesives. The multilayer structure of the present invention can further include other layers, in some embodiments, including, for example, biaxially oriented polyamide films, biaxially oriented polyethylene terephthalate films, biaxially oriented polypropylene films, ethylene vinyl alcohol films, polyvinylidene chloride films, metallized biaxially oriented polyamide films, metallized biaxially oriented polyethylene terephthalate films, metallized biaxially oriented polypropylene films, and / or other films.
[0065] It should be understood that any layer, film, or adhesive of the multi-layer structure may further include one or more additives known to those skilled in the art, such as, for example, antioxidants, UV stabilizers, heat stabilizers, slip agents, antiblock agents, antistatic agents, pigments or colorants, processing aids, crosslinking catalysts, flame retardants, fillers, and blowing agents. For example, in embodiments, the sealant film includes at least one of a slip agent or an antiblock agent.
[0066] The multilayer structure of the present invention can have advantageous properties. For example, the multilayer structure according to the embodiments disclosed herein has a significantly higher adhesive bond strength compared to other multilayer structures. In an embodiment, the multilayer structure has an adhesive bond strength of at least 2.5 N / 15 mm, and the adhesive bond strength can be measured according to the test method described below. All individual values and subranges of at least 2.5 N / 15 mm are disclosed and included herein. For example, the multilayer structure can have an adhesive bond strength of at least 2.5 N / 15 mm, at least 3.0 N / 15 mm, at least 3.5 N / 15 mm, at least 4.0 N / 15 mm, or at least 4.5 N / 15 mm, and the adhesive bond strength can be measured according to the test method described below.
[0067] Embodiments of the present invention also provide articles formed from any of the multi-layer structures described herein. Examples of such articles include packaging, flexible packaging, pouches, and labels. In some embodiments, the packaging of the present invention may contain liquids, powders, food, or other items. The articles and packaging of the present invention may be formed from the multi-layer structures disclosed herein using techniques known to those of skill in the art in view of the teachings herein.
[0068] Test Method density Density is measured in grams per cubic centimeter (g / cc or g / cm) according to ASTM D792. 3 )
[0069] Melt Index (I2) Melt index (I2) is measured at 190°C and 2.16 kg (except for propylene-based polymers) according to ASTM D-1238. Melt index for propylene-based polymers is measured at 230°C and 2.16 kg according to ASTM D-1238. Melt index values are reported in g / 10 min, which corresponds to grams dissolved per 10 minutes.
[0070] Storage Modulus The sample resins are pressed into tablets (60 mm x 60 mm x 1 mm) by an injection molding machine (FANUC™, S-2000i100BH, screw diameter = 28 mm). The processing parameters are reported in Table 1.
[0071] [Table 1]
[0072] The tests are carried out on a TA Instruments RSA-G2 machine using a tension rectangle. Method parameters: 1. Oscillation temperature gradient 2. Temperature from 35 to 180°C at 3°C / min 3. Angular frequency of 6.28rad / s 4. 0.1% distortion.
[0073] Gloss Gloss is measured at a 45° angle according to ASTM D2457.
[0074] Turbidity Haze is determined according to ASTM D1003.
[0075] Adhesive Bond Strength Test The sample film is cut into 15 mm wide strips for T-peel testing on an Instron 5943 machine at a crosshead speed of 250 mm / min. Three strips are tested to obtain an average value. During the test, the tail of the strip is pulled slightly with a finger to ensure that the tail is maintained at a 90 degree angle to the peel direction.
[0076] Heat seal initiation temperature and seal strength To determine the heat seal initiation temperature (HSIT) and seal strength, the samples are sealed by a J&B Hot Tack 4000 Tester with a protection of 12 μm PET film on the sample film skin. The sample width is 25 mm, the dwell seal time is 0.5 seconds, and the seal pressure is 0.275 N / mm. 2 The heat sealed samples are conditioned for 24 hours and then measured using a Zwick tensile machine equipped with a 200N load cell and a pull rate of 500mm / min. The HSIT is reported as the minimum temperature in degrees Celsius to reach 5 Newtons force per 25mm. Seal strength values are reported in N / 25mm. EXAMPLES
[0077] The following examples illustrate features of the present disclosure and are not intended to limit the scope of the disclosure.
[0078] Sealant Film The three-layer sealant film is coextruded by a conventional polyethylene blown film process. The composition of the film is shown in Table 2 below. The film has a layer ratio of 3 / 4 / 3 and a total thickness of 60 μm (so that the layer thicknesses are 18 microns / 24 microns / 18 microns). The heat seal strength data of the sealant film is shown in Table 3 below. As shown, the heat seal initiation temperature (HSIT) of the sealant film is less than 100° C.
[0079] The following materials were used in the preparation of the sealant films: INNATE™ TH60, a polyethylene resin having a density of 0.912 g / cc and a melt index, I2, of 0.85 g / 10 min, commercially available from The Dow Chemical Company, Midland, Mich. ELITE™ AT 6202, a linear low density polyethylene having a density of 0.908 g / cc and a melt index, I2, of 0.85 g / 10 min, commercially available from The Dow Chemical Company, Midland, Mich. AFFINITY™ PL1881G, a polyolefin plastomer having a density of 0.904 g / cc and a melt index, I2, of 1 g / 10 min, commercially available from The Dow Chemical Company (Midland, Mich.). LDPE 2426H, low density polyethylene commercially available from CNOOC and Shell Petro-Chemical (China). White Master Batch 7M1508 available from Shang Hai JinZhu Master Batch Company (China).
[0080] [Table 2]
[0081] [Table 3]
[0082] Biaxially oriented polyethylene film (BOPE) film As a comparative example, a BOPE film having a glossy (smooth) surface on both skin layers (hereinafter referred to as "BOPE gloss") is used. The BOPE gloss film is commercially available from Guangdong Decro Film New Materials Co. Ltd. The BOPE gloss film is INNATE™ TF 80 with a density of 0.926 g / cc and a viscosity of 1.7 g / 10 min. The BOPE gloss film is made of linear low density polyethylene having a melt index of I2 and commercially available from The Dow Chemical Company, Midland, MI. The BOPE gloss film has a thickness of 25 microns (after stretching). The gloss of the BOPE gloss film at the skin layer surface is 86.7% and the haze of the BOPE gloss film at the skin layer surface is 2.4%. The machine direction (MD) stretch ratio of the BOPE gloss film is 4:1 and the transverse direction stretch ratio of the BOPE gloss film is 8:1.
[0083] In the embodiment of the present invention, a BOPE film (hereinafter referred to as "BOPE mat") is formed, which includes a skin layer having a matte surface, a core having one core layer, and an outer layer. The BOPE mat film is formed on a tenter frame biaxial stretching line. The tenter frame line has a three-layer coextrusion line. The output ratio of the three extruders is 1:8:1. After extrusion from the flat die, the film is cooled on a chill roll and immersed in a water bath filled with room temperature water. The cast film is then passed over a series of rollers with different rotation speeds to achieve machine direction (MD) stretching. There are three pairs of rollers in the MD stretching segment of the production line, all of which are oil heated. The first pair of rollers is preheated. The second pair is a stretching roller. The last pair of rollers is for relaxation and annealing. The temperature of each pair of rollers is controlled separately. After MD stretching, the film web is passed through a tenter frame hot air oven containing seven heating zones to perform transverse direction (CD) stretching. The first three zones are for preheating, the next two zones are for stretching. The last two zones are for annealing. The temperature of each zone is controlled separately. The CD stretch ratio of this tenter frame line is fixed at 8x. The MD stretch ratio is fixed at 4x. Thus, the BOPE matte film is stretched in the machine direction with a stretch ratio of 4:1 and in the transverse direction with a stretch ratio of 8:1.
[0084] The BOPE matte film has a thickness of 25 microns (after stretching). The core and outer layers of the BOPE matte film consist of INNATE™ TF 80. The skin layer, which has a matte surface, consists of a blend of 50% by weight ELITE™ 5815 and 50% by weight TOPILENE PPR R200P. ELITE™ 5815 is an ethylene-based polymer, specifically 0.910 g / cc and a melt index (I2) of 15 g / 10 min, and is commercially available from The Dow Chemical Company (Midland, MI). TOPILENE PPR R200P is a propylene-based polymer, specifically a propylene random copolymer, having a density (ASTM D792) of 0.90 g / cc and a melt index (ASTM D1238, 230°C / 2.16 kg) of 0.25 g / 10 min, and is commercially available from Hyosung Corporation. TOPILENE PPR R200P has a storage modulus of 124 MPa at 110.0°C and 77.8 MPa at 120°C. ELITE™ 5815 has a storage modulus of about 0 MPa at 110° C. and about 0 MPa at 120° C., so the difference in storage modulus between ELITE™ 5815 and TOPILENE PPR R200P is 124 MPa at 110.0° C. and 77.8 MPa at 120° C. The skin layer with a matte surface is 10% of the total BOPE matte film thickness. The gloss of the matte surface of the skin layer is 12.3% and the haze of the matte surface of the skin layer is 51.3%.
[0085] multilayer structure The sealant film formed as above is laminated to a BOPE gloss film for the comparative examples and to a BOPE matte film for the inventive examples. The sealant film is adhesively laminated to each BOPE film to form a multi-layer structure. One set of multi-layer structures is produced by a manual adhesive lamination process. Another set of multi-layer structures is produced by a mechanical adhesive lamination process. In the inventive examples, the adhesive is coated on the matte surface of the skin layer of the BOPE matte film and adhered to layer 1 of the sealant film (i.e., the layer containing 100% INNATE™ TH60). In the comparative examples, the adhesive is coated on either glossy side of the BOPE gloss film (having the same composition) and adhered to layer 1 of the sealant film (i.e., the layer containing 100% INNATE™ TH60).
[0086] MOR-FREE™ 709A / B, ROBOND™ L168 / CR3A, ROBOND™ L188 / CR3A, ADCOTE™ D516A / F, and ADCOTE™ 545S / F are the adhesives used and are each commercially available from The Dow Chemical Company, Midland, Mich. MOR-FREE™ 709A / B is a solvent-free adhesive, ROBOND™ L168 / CR3A and ROBOND™ L188 / CR3A are water-based adhesives, and ADCOTE™ 545S / F and ADCOTE™ D516A / F are solvent-based adhesives.
[0087] For the manual adhesive lamination process, a laboratory drawdown on a K-Coater (Model 101, RK Print-Coat Instruments Ltd.) is used using appropriate application rods to achieve a common coating weight for different types of adhesives. Hand lamination with a Hot Roll Laminator, HR-101, Chem-Instruments Ltd. is used with a pressure of 40 psi and a nip temperature of 150°F.
[0088] For the mechanical adhesive lamination process, a Nordmeccanica line (type: LABO COMBI 400) is used with the parameters specified in Table 4 below.
[0089] [Table 4]
[0090] Table 5 below provides the constructions, adhesives, and adhesive coating weights of inventive and comparative examples prepared by a manual adhesive lamination process. Table 6 below provides the constructions, adhesives, and adhesive coating weights of inventive and comparative examples prepared by a mechanical adhesive lamination process.
[0091] [Table 5]
[0092] [Table 6]
[0093] The adhesive bond strength of each of the inventive examples and comparative examples is measured according to the above-mentioned test method. Table 7 provides the results. As can be seen from the results, the adhesive bond strength of the inventive examples is significantly stronger. From the test, it is also observed that in the inventive examples, the adhesive sticks to the matte surface of the skin layer and does not stick to the sealant film, while in the comparative examples, the adhesive sticks to the sealant film.
[0094] [Table 7]
[0095] All documents cited herein, including any cross-referenced or related patents or applications, if any, and any patent applications or patents to which this application claims priority or the benefit thereof, are incorporated herein by reference in their entirety, unless expressly excluded or otherwise limited. The citation of any document is not admitted as prior art with respect to any invention disclosed or claimed herein, or as teaching, suggesting, or disclosing such invention, either alone or in any combination with any other reference. Furthermore, to the extent that a meaning or definition of any term in this document conflicts with any meaning or definition of the same term in a document incorporated by reference, the meaning or definition assigned to that term in this document shall govern.
[0096] While particular embodiments of the present invention have been illustrated and described, it would be obvious to those skilled in the art that various other changes and modifications can be made without departing from the spirit and scope of the invention. Therefore, it is intended in the appended claims to cover all such changes and modifications that are within the scope of this invention.
Claims
1. A multi-layer structure comprising: (a) a biaxially oriented polyethylene film comprising a skin layer having a matte surface and a core, the core comprising one or more core layers; the matte surface having either or both of: (1) a gloss of less than 50% as measured by ASTM D2457 at a 45° angle; and (2) a haze of greater than 45% as measured by ASTM D1003; a biaxially oriented polyethylene film having two skin layers, including one skin layer having the matte surface, and at least one core layer; (b) a sealant film; and (c) an adhesive that adheres the sealant film to the matte surface of the skin layer of the biaxially oriented polyethylene film.
2. 10. The multilayer structure of claim 1, wherein the skin layer comprises 20 to 80 weight percent of an ethylene-based polymer and 80 to 20 weight percent of a propylene-based polymer, based on a total weight of the skin layer, and wherein the ethylene-based polymer and the propylene-based polymer each have a storage modulus, and the difference in the storage modulus between the ethylene-based polymer and the propylene-based polymer is greater than 40 Megapascals (MPa) at 110°C and greater than 18 MPa at 120°C.
3. 2. The multilayer structure of claim 1, wherein the skin layer comprises an ethylene / α-olefin copolymer and a propylene / ethylene copolymer, each of the ethylene / α-olefin copolymer and the propylene / ethylene copolymer having a storage modulus, the difference between the storage modulus of the ethylene / α-olefin copolymer and the propylene / ethylene copolymer being 110 to 130 megapascals (MPa) at 110° C. and 70 to 80 MPa at 120° C., and the matte surface of the skin layer has (i) a gloss of 3% to 15% as measured by ASTM D2457 at a 45° angle, or (ii) a haze of greater than 45% as measured by ASTM D1003.
4. The multilayer structure of any one of claims 1 to 3, wherein the core comprises at least 50 weight percent ethylene-based polymer, based on the weight of all the core layers.
5. 5. The multilayer structure of any one of claims 1 to 4, wherein the biaxially oriented polyethylene multilayer film has a thickness and the core comprises at least 50% of the film thickness.
6. 6. The multilayer structure of any one of claims 1 to 5, wherein the biaxially oriented polyethylene film is stretched in the machine direction with a stretch ratio of from 2:1 to 6:1 and in the transverse direction with a stretch ratio of from 2:1 to 9:
1.
7. 7. The multilayer structure of any one of claims 1 to 6, wherein the matte surface of the skin layer has a haze of greater than 45% as measured by ASTM D1003.
8. The multi-layer structure of any one of claims 1 to 7, wherein the skin layers comprise an ethylene-based polymer having a density of 0.900 to 0.960 g / cc, the density being measured according to ASTM D792.
9. 9. The multilayer structure of any one of claims 1 to 8, wherein the sealant film comprises a layer comprising at least 20% by weight of a polyolefin plastomer, a polyolefin elastomer, a very low density polyethylene, an ethylene acetate copolymer, an ethylene acrylic acid copolymer, or an ethylene acrylate copolymer, based on the total weight of the layer.
10. A multilayer structure described in any one of claims 1 to 9, wherein the sealant film has a heat seal initiation temperature of less than 120°C.
11. The multilayer structure of any one of claims 1 to 10, wherein the adhesive comprises a solventless adhesive, a water-based adhesive, or a solvent-based adhesive.
12. A multilayer structure described in any one of claims 1 to 11, wherein the adhesive bond strength of the multilayer structure is at least 2.5 N / 15 mm.
13. An article comprising the multilayer structure of any one of claims 1 to 12.
Citation Information
Patent Citations
Biaxially-oriented polyethylene multilayer film with a matte surface
WO2020001191A1
